Carbon Emissions In Asia: The Role Of Renewable Energy, Non-Renewable Energy, Carbon Tax, And Net-Zero Emissions Commitments - Kenley Maccauley Riyono; Luky Patricia Widianingsih (UNIVED Press, 2025)
Net-zero emissions are the main target for countries to immediately address the current carbon emission problem due to the degradation of the natural environment. Asia is the largest emitter of carbon emissions and the largest user of energy. Most of these carbon emissions result from the excessive use of non-renewable energy as the main energy input. Renewable energy is believed to have a dual effect of reducing carbon emissions and replacing the role of non-renewable energy. The transition is an important issue nowadays for countries supported by domestic climate policies and country commitments. The purpose of this study is to determine whether renewable energy, non-renewable energy, carbon tax, and net-zero emissions will affect carbon emissions. The results show that renewable energy and net-zero emissions have a negative significant effect, non-renewable energy has a positive significant effect, and carbon emission has no significant effect on carbon emissions in Asia. Even so, the implication of this research is as input and consideration for countries to transition to sustainable energy sources and strengthen the design of carbon tax to be more effective along with the country's commitment. The sample used is 36 countries in Asia from 2011-2020. The method used is panel data analysis to determine the effect.